1997
DOI: 10.1080/713613156
|View full text |Cite
|
Sign up to set email alerts
|

Sexuality in Montreal women living with HIV

Abstract: The impact of learning a positive HIV test result on the sexuality of 161 women (47 injection drug users (IDU), 53 non-IDU women of Haitian or African origin (non-IDU-HA), and 61 non-IDU Caucasian women (non-IDU-C) was assessed using closed and open-ended questions. Self-reported CD4+ count correlated with any post-test (p = 0.001) and past month sexual activity (p = 0.007). After learning their HIV status, 110 women (68%) were sexually active, 48 (44%) of these within 1 month. After resuming sexual activity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
42
0
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 0 publications
2
42
0
2
Order By: Relevance
“…9 Pesquisa entre as mulheres HIV-positivas nos paí-ses industrializados sugere que o diagnóstico pode interromper a vida sexual, 17 mas a maioria das mulheres e homens mantém sua atividade sexual apesar da angústia que sobrevém ao diagnóstico da infecção pelo HIV. 19 A atividade sexual é uma questão muito importante e está freqüentemente relacionada ao amor e à afetividade, e não somente à questão da procriação. 26 Esses sentimentos românticos se contrapõem, na prática, às medidas preconizadas para a prevenção das DST/Aids.…”
Section: Discussionunclassified
“…9 Pesquisa entre as mulheres HIV-positivas nos paí-ses industrializados sugere que o diagnóstico pode interromper a vida sexual, 17 mas a maioria das mulheres e homens mantém sua atividade sexual apesar da angústia que sobrevém ao diagnóstico da infecção pelo HIV. 19 A atividade sexual é uma questão muito importante e está freqüentemente relacionada ao amor e à afetividade, e não somente à questão da procriação. 26 Esses sentimentos românticos se contrapõem, na prática, às medidas preconizadas para a prevenção das DST/Aids.…”
Section: Discussionunclassified
“…In a longitudinal study of HIV-positive women in the military (Brown, Kendall, & Ledsky, 1995), 21% of women met the criteria for HSDD at the initial evaluation, but 50% met the criteria at both the second and third evaluations 6 to 18 months later. Among those who continued to engage in sexual activity, low levels of sexual satisfaction have been documented, with 32% of HIV-positive women in Canada reporting they were not satisfied or only a little satisfied with their sex lives (Hankins et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Although lower than that found among older women, sexual abstinence following HIV diagnosis has also been found to be quite common among younger HIV-positive women. For example, studies have found that 32% of HIV-positive women in Canada were no longer sexually active following their HIV diagnosis (Hankins, Gendron, Tran, Lamping, & Lapointe, 1997), that 42% of HIV-positive women in New England reported not having had sex in the past month (Bova & Durante, 2003), and that 34% of HIV-positive women with a history of injecting drug use avoided sex due to their HIV infection (Meyer-Bahlburg et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While most people living with HIV practice safer sex or abstinence, at least 20-30% continue to engage in risky sexual practices and this proportion appears to be increasing. [4][5][6][7][8][9][10][11][12][13][14][15][16] Based on these data, policymakers have recommended that interventionists develop strategies to reduce risky sexual behaviors of HIVinfected people. [17][18][19][20][21][22][23][24] In the past, the few safer sex interventions that targeted HIV-infected people met with limited success because they often did not address issues of serostatus disclosure, HIV stigma, or motivation to protect others from HIV.…”
mentioning
confidence: 99%